Robo-Advisor Model Adoption: A Digital Transformation To Accelerate Continuance Usage of Islamic Banking Product - Reni Furwanti; Dini Maulana Lestari; Dhika Dzulkarnain Wibisono (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2025)
As Islamic banking becomes one of vital sectors in driving National economic growth, accelerating its development is prominent. The use of Robo-Advisor in this sector can help Islamic banking increase its existence and market share to compete in a global financial market. This research aims to conduct a model for the adoption of Robo-Advisor in Islamic banking sector to accelerate continuance intention usage of Islamic banking product in Indonesia by exploring the role of sharia financial literacy and halal awareness as mediating variables. This is explanatory research with quantitative and survey method. This research picks Islamic banking users in Indonesia, using quota sampling technique to achieve a representative sample in each province of Indonesia, resulting in 403 respondents. Structural Equation Model (SEM-PLS) is used to analyze the data and the relationship among variables. Empirically, the result revealed that the Robo-Advisor model adoption significantly accelerates the continuance intention usage of Islamic banking product in Indonesia. This research contributes in broadening horizon in terms of Islamic banking continuance usage by proposing integrated model. Furthermore, this research recommends the implementation of Robo-Advisor as a digital transformation for Islamic banking sector to support the growth of Islamic financial industry in Indonesia, remembering that Robo-Advisor is currently not used in either Islamic or conventional banking sectors.